Laparoscopic distal pancreatectomy of a solid pseudopapillary tumour in a teenager after size reduction: A case report - Eun-jung Koo; Hyunji Lee; Eunyoung Jung; Soon-Ok Choi (Elsevier, 2017)
A solid pseudopapillary tumour (SPT) of the pancreas is very rare in children. Despite its malignancy potential, SPT is known to have a good prognosis. No prior report has described the use of neoadjuvant chemoradiation with retinoid therapy for size reduction of an SPT before surgical excision. An 11-year-old girl had intermittent abdominal pain and a huge mass occupying the whole abdomen. The plain abdominal radiograph and abdominal computed tomography scan showed a 16-cm, huge pancreatic mass across the midline. An ultrasonography-guided biopsy was performed, and pathological examination confirmed an SPT of the pancreas. As the mass was adjacent to large vessels, chemoradiotherapy was preferred to surgical resection. After 1 year of chemoradiotherapy, the tumour decreased to 14 cm. Three years of immunotherapy with retinoic acid reduced the tumour to 10 cm. Laparoscopic distal pancreatectomy was performed after the size of the tumour had decreased. The tumour was successfully excised, and the pathological examination confirmed an SPT of the pancreas without malignant characteristics. The patient's postoperative clinical course was uneventful; there was no evidence of recurrence or metastasis during the 16-monthfollow-up. Surgical resection is a reliable treatment for SPTs; however, a second option needs to be used when operation is inappropriate. In our case, subsequent laparoscopic distal pancreatectomy was successful.